Water resource models in the Mekong Basin: A review - Johnston, R.; Kummu, M. (Springer, 2012)
Development of the water resources of the Mekong Basin is the subject of intense debate both within the Mekong region and internationally. Water resources modelling is playing an increasingly important role in the debate, with significant effort in building integrated modelling platforms to describe the hydrological, ecological, social and economic impacts of water resource development. In the hydrological domain, a comprehensive set of models has been effective in building understanding of the system, and in identifying and describing the issues and trade-offs involved in basin-scale water planning. In the ecological and social domains, quantitative modelling has not progressed very far; geo-spatial analysis and qualitative frameworks remain the most commonly used tools. Economic models have been used to assess the costs and benefits of water resources development and to describe the trade-offs between different sectors and users. These analyses are likely to play an important role in the policy and planning debate, but are hampered by uncertainties in valuation of ecosystem services. Future efforts should focus on optimising the use of existing model platforms for the Mekong, including structured comparison of multiple hydrological models to quantify errors and identify an optimum set of modelling tools for different applications. A comprehensive research effort is needed to incorporate groundwater into hydrological models for regional planning. Options for social impact assessment should be reassessed before major investments are made in complex modelling platforms, and participatory social survey methods evaluated as part of an integrated assessment framework.